Persoanele cu probleme de sănătate mintală în România: stereotipuri, cauze şi modalităţi de îngrijire percepute, atitudini şi distanţă socială - Stănculescu, Manuela Sofia; Niţulescu, Dana; Preotesi, Mihnea; Ciumăgeanu, Mugur; Sfetcu, Raluca (Calitatea Vieții, 2008)
This study presents the main results of a sociological research regarding public conceptions and attitudes toward persons with mental health problems. According to this analysis, in Romania there is a consistent knowledge deficit with respect to mental health related concepts. The Romanian population is reticent in applying the label “mental illness”, but, at least at the public perception level, the former patients of mental hospitals have to face devaluation and discrimination more severe than in countries such as Germany, Russia or Slovakia. The large majority of the population knows to identify a mental health problem, but do not usually put this knowledge into practice.